2021
DOI: 10.3390/md19030171
|View full text |Cite
|
Sign up to set email alerts
|

EPS364, a Novel Deep-Sea Bacterial Exopolysaccharide, Inhibits Liver Cancer Cell Growth and Adhesion

Abstract: The prognosis of liver cancer was inferior among tumors. New medicine treatments are urgently needed. In this study, a novel exopolysaccharide EPS364 was purified from Vibrio alginolyticus 364, which was isolated from a deep-sea cold seep of the South China Sea. Further research showed that EPS364 consisted of mannose, glucosamine, gluconic acid, galactosamine and arabinose with a molar ratio of 5:9:3.4:0.5:0.8. The relative molecular weight of EPS364 was 14.8 kDa. Our results further revealed that EPS364 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…And it is discovered that Moringa oleifera fruit could cause ROS-mediated apoptosis in human liver cancer HepG2 cells [44]. What is more, Wang et al demonstrated that EPS364, a deep-sea bacterial exopolysaccharide, exhibited an antitumor trait by inducing hepatic cell death by upregulating ROS production, supporting the idea that oxidative stress could trigger cell death [45]. And the idea is likewise proofed by another research where diTFPP/C2-ceramide increased hepatic cell death by increasing ROS levels [39].…”
Section: Irisin Decreases Er Stressmentioning
confidence: 99%
“…And it is discovered that Moringa oleifera fruit could cause ROS-mediated apoptosis in human liver cancer HepG2 cells [44]. What is more, Wang et al demonstrated that EPS364, a deep-sea bacterial exopolysaccharide, exhibited an antitumor trait by inducing hepatic cell death by upregulating ROS production, supporting the idea that oxidative stress could trigger cell death [45]. And the idea is likewise proofed by another research where diTFPP/C2-ceramide increased hepatic cell death by increasing ROS levels [39].…”
Section: Irisin Decreases Er Stressmentioning
confidence: 99%
“…Gelling agent Metal-complexion Antioxidant [220] Vibrio alginolyticus 364 deep-sea Anti-tumour [223] Rhodothermus marinus DSM 4252 T Shallow marine hot springs Antioxidant Anti-haemolytic Anti-thrombotic [224] Winogradsky sp. CAL384 and Shewanella sp.…”
Section: Sphingobium Yanoikuyae Bbl01 Coastmentioning
confidence: 99%
“…Extraction of total RNA and synthesis of cDNA were performed as mentioned previously (45). The full-length cDNA sequence of β1-integrin was obtained by PCR.…”
Section: Dna Constructs Transfection and Overexpressionmentioning
confidence: 99%